2014
DOI: 10.1111/odi.12249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the neuropeptides vasoactive intestinal peptide, peptide histidine methionine and substance P on human major salivary gland secretion

Abstract: Vasoactive intestinal peptide and PHM, but not SP, are likely transmitters in the parasympathetic control of salivary (protein) secretion in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…The present study shows that melatonin is located in the secretory granules of the acinar serous cells of the rat parotid gland and therefore is likely to be released by exocytosis into the lumen, as a consequence of the mobilization of the major regulated secretory pathway (Castle & Castle, 1996). Exocytosis by the b-adrenergic receptor agonist, isoprenaline, is a well known phenomenon in salivary glands, having been demonstrated not only in rodents (Amsterdam et al 1969;Peter et al 1995) but also in humans (Testa Riva et al 2006;Del Fiacco et al 2015). The present findings thus suggest a role for sympathetic activity, by badrenergic receptors, in the secretion of melatonin.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The present study shows that melatonin is located in the secretory granules of the acinar serous cells of the rat parotid gland and therefore is likely to be released by exocytosis into the lumen, as a consequence of the mobilization of the major regulated secretory pathway (Castle & Castle, 1996). Exocytosis by the b-adrenergic receptor agonist, isoprenaline, is a well known phenomenon in salivary glands, having been demonstrated not only in rodents (Amsterdam et al 1969;Peter et al 1995) but also in humans (Testa Riva et al 2006;Del Fiacco et al 2015). The present findings thus suggest a role for sympathetic activity, by badrenergic receptors, in the secretion of melatonin.…”
Section: Discussionsupporting
confidence: 63%
“…Scale bar: 1 lm. the co-transmitter of acetylcholine, vasoactive intestinal peptide, evoke exocytosis, demonstrating a regulatory role in this process for parasympathetic transmitters in both animals (Ekstr€ om et al 1994;Ekstr€ om & Ekstr€ om, 2001;Ekstr€ om, 2002) and humans (Del Fiacco et al 2015). In agreement with the exocytotic responses to autonomimetics, animal experiments show varying degrees of acinar granule depletion in response to the electrical stimulation of the sympathetic and parasympathetic innervations (Garrett & Thulin, 1975;Ekstr€ om et al 1994Ekstr€ om et al , 1996.…”
Section: Discussionmentioning
confidence: 64%
“…Beside the traditional transmitters of the parasympathetic and sympathetic postganglionic nerves, acetylcholine and noradrenaline, respectively, a number of co‐transmitters may occur in cholinergic and adrenergic axons, of which some induce secretion themselves or potentiate the effects of the classical transmitters . Particular attention has been paid to the parasympathetic innervation and a number of neuropeptides as potential co‐transmitters, one of which is vasoactive intestinal peptide (VIP), causing secretion of proteins but only a small fluid secretion, if any, and moreover, vasodilatation …”
Section: Neural Regulation Of Salivary Secretion and The Secretory Elmentioning
confidence: 99%
“…Furthermore, Del Fiacco et al (2014) have revealed that besides VIP-positive axons, also PHM-immunoreactive nerve terminals found in close proximity to acini and ducts are relatively abundant in the human MGl. Therefore, in humans these peptides may play a more active part in the regulation of the secretion of saliva in the mucous acini than in the serous acini.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in a variety of species including the rat, mouse, cat, ferret and humans that nerve fibres innervating the MGl may contain biologically active substances, including vesicular acetylcholine transporter (VAChT; cholinergic marker), neuronal nitric oxide synthase (nNOS), vasoactive intestinal polypeptide (VIP), pituitary adenylate cyclase activating peptide (PACAP), VIPrelated peptide histidine methionine (PHM), neuropeptide Y (NPY), somatostatin (SOM), galanin (GAL), Met5-enkephalin (Met-ENK), substance P (SP) and calcitonin gene-related peptide (CGRP) (Soinila et al 1989;Tobin et al 1990;Shida et al 1991;Hauser-Kronberger et al 1992;Lohinai et al 1995;Tobin et al 1995;Alm et al 1997;Jia et al 1997;Kusakabe et al 1997;Takai et al 1999;Del Fiacco et al 2014). Although relatively much is known about the innervation of the MGl, it should be emphasised that the studies mentioned above have mostly focused on laboratory mammals and humans.…”
mentioning
confidence: 99%